Modification of Pt-Porous Composite Material (Pt-PCM) and Its Application for Electroanalysis of Uric Acid and Electrosynthesis of Acetic Acid from Ethanol - Riyanto; Nurhasanah; Mohamed Rozali Othman (Science and Technology Indonesia, 2023)
Research on the synthesis of Pt-Porous Composite Material (Pt-PCM) has been done. This material is used for the electrochemical activity of uric acid and electrochemical synthesis of acetic acid from ethanol. Pt-PCM is made by mixing 99.995% platinum powder and PVC or Poly (vinyl chloride) homogeneously with a homogenizer for 3.0 h, plus tetrahydrofuran solvent, and pressed with a strength of 10 tons/cm2. The material produced was analysis using Scanning Electron Microscopy (SEM), voltammetry potential V and Tafel plot. The material is used as an electrode for the determination of uric acid and the synthesis of acetic acid from ethanol. The results showed that Pt-PCM has evenly distributed pores and has a perfect Tafel slope compared to metal platinum or solid platinum. Pt-PCM also has the excellent ability as a working electrode for the analysis of uric acid in human urine and electro synthetic acetic acid from alcohol. In conclusion, Pt-Porous Composite Material (Pt-PCM) is a porous material, so it is excellent as a candidate for electrodes.